Penatalaksanaan Pemeriksaan Foramen Orbita Posisi Rhese Methode Dengan Kasus Selulitis - Dewi Febriyanti; Pocut Zairiana Finzia; M. Maula Ziqri3 (STIKes Ibnu Sina Ajibarang, 2024)
One of the schedell examinations includes the examination of the orbital foramen, which aims to provide information on the presence or absence of abnormalities in the orbital region. Common abnormalities in the orbital foramen include foreign bodies, fractures, cellulitis, and tumors. This research is descriptive in nature, aiming to provide a complete description and explanation of the imaging of the orbital foramen. The study was conducted at the Radiology Department of Pertamedika Ummi Rosanti, Banda Aceh. The results of the study indicate that in the Rhese Method AP with a 37-degree angle of the orbital foramen in cases of cellulitis, there is no clear visualization of the mass in the orbital cavity, making it appear normal. Therefore, it can be concluded that for cellulitis cases, the Rhese Method AP and PA with 37-degree and 53-degree angulations are not suitable